The end of the world - Rabkin, Eric S.; Greenberg, Martin Harry; Olander, Joseph D. (Alternatives., 1983)
Book Description: Wolfe sees in these postholocaust narratives a central attraction- "the mythic power inherent in the very conception of a remade world." This power derives from three sources: the emergence of a new order from the ashes of the old system, and thus a kind of denial of death; the reinforcement of one set of values as opposed to another; and as something always replaces whatever was destroyed, a promise that nothing can annihilate humanity